Enhancement of visible-light photocatalytic activity of Cu-doped TiO2nanoparticles - Paruchai Pongwan (2018)
© 2015 Springer Science+Business Media Dordrecht. Bare TiO2and Cu-doped TiO2nanoparticles with different nominal doping amounts of Cu ranging from of 0.5 to 5.0 mol% were synthesized using the modified sol-gel method. The samples were physically characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, Brunauer-Emmett-Teller-specific surface area, UV-Vis diffuse reflectance spectroscopy, zeta potential, X-ray photoelectron spectroscopy, inductively coupled plasma, and photoluminescence techniques. The Cu-doped TiO2exhibited good photocatalytic activity in mineralization of oxalic acid and formic acid under visible light irradiation. Photomineralization of oxalic and formic acids under visible light irradiation revealed greatly enhanced photoactivity exhibited by the 2.0 mol% Cu-doped TiO2photocatalyst compared to bare TiO2. The enhanced photocatalytic performance arises from copper ion doping in the TiO2structure, leading to an extended photoresponsive range, enhanced photogenerated charge separation, and transportation efficiency.